Peran Mental Toughness terhadap Competitive Anxiety pada Pemain Futsal - Insan, Imammul (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Mental Toughness and Competitive Anxiety become psychological factors in sports because especially the players are teenagers. Research on sports psychology is currently developing so it is interesting to study especially on futsal players. Thus, this study aims to examine the effect of mental toughness on competitive anxiety in futsal players. This research is in the form of a survey (n=80) on futsal players in Sumbawa Besar City. Simple regression analysis was used to determine the effect of mental toughness on competitive anxiety in futsal players. The results showed that mental toughness had a significant effect on competitive anxiety. Thus, futsal players who have high mental toughness will reduce competitive anxiety that arises when competing. The findings of this study provide input to the Futsal Association (AFKAB) of Sumbawa Regency to prioritize mental strengthening programs for futsal players so that they are more optimal when competing.